Search and identification of high-velocity stars by dynamicalejection and supernovae from multiple stars - Hambaryan, V.; Neuhaeuser, R.
The project, funded by Science Committee of RA (ARPI program), intended to search, detection, kinematic study and identification of the birth places of the high-velocity and isolated neutron stars that encountered in the past with a stellar groups (multiple stars, stellar clusters, associations, etc.) closer than 10 pc, i.e. to test the concept: a high-velocity star and a stellar group or some of its members in the past were “in the same place at the same time”. We plan to use stars with the high-quality astrometry and radial velocities from the very recently released Gaia DR3 catalogue and empirically select high-velocity candidates. Next, by using full gravitational potential of the Galaxy to calculate the motion of a stellar groups and a candidate of high-velocity star from their current positions to the proximity epoch. For numerical integration we will utilize the fast and accurate numerical integration.
Keywords: Astronomy